Awerroes i esencjalna reinterpretacja metafizyki Arystotelesa - Kokoć, Damian (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
Question of relation between an essence and an existence was one of major medieval philosophical problems. The first ones who started considerate this issue were Muslim thinkers, especially Avicenna and Averroes. The latter of them was one of the main figure in this debate. Étienne Gilson claims that on ground of Averroes’ thought Aristotle struggles with problem of existence. Averroes claimed that this two components differ only in logical manner. In reality an essence and an existence are identical and an existence is something which flows from essence of being. That is why Averroes did not agree with Avicenna that existence is only a accident of essence, because such claim is contradictory with Aristotle’s theory of being. According to this Greek thinker, all accidents can be described by one of the categories (except a category of substance which is the subject on which other categories are predicated) and an existence is not one of them. For Averroes, Avicenna‘s conception is example of contamination of Aristotle’s thought by theological components. That is why he tried to purify interpretations of Aristotle’s philosophy from this ideas, foreign to his thought. According to Averroes problem of relation between an essence and an existence is wrongly formulated because when we want explain why the being is, we must only point on it cause and we don’t need to search answer about an existence of being.